METACOGNITIVE BELIEFS AS DETERMINANT OF IMPOSTOR PHENOMENON AMONG UNIVERSITY STUDENTS IN KARACHI, PAKISTAN - Mukhtar, Hira; Bano, Nasreen; Shahzad, Salman (Journal of Pakistan Psychiatric Society, 2024)
OBJECTIVE: The purpose of current research is to explore the association between metacognitive skills and impostor phenomenon in University students. BACKGROUND: Dysfunctional metacognitions include in the etiological factor of mental health problems[1]. Metacognitions have importance to maintain and increases worry and anxiety[2]. Likewise, same approach plays important role in the development of impostor phenomenon which also involves anxiety and worries related to self-doubt, and leading an individual mental health difficulties and maladaptive coping mechanisms. STUDY DESIGN Quantitative Survey design PLACE AND DURATION OF STUDY Present study was conducted in Karachi, Pakistan from July- September, 2016. SAMPLE AND METHOD: The convenient sampling was employed to recruit the sample of 199 (85 males and 114 females) university students, age ranging from 18 to 25 years (Mean=20.52, SD=1.52) from different Universities of Karachi, Pakistan. MEASURES: To assess the variables Well’s Metacognitive Beliefs Questionnaire[3] and Clance Impostor Phenomenon Scale [4] were used. RESULTS: The findings indicated that metacognitive beliefs significantly predict impostor phenomenon (R2= .283, F=15.316, p<.01) particularly “negative beliefs about uncontrollability and danger of worry” (t= 2.60, P <0.05), “Cognitive Control” (t= 2.19, P <0.05), and “need for control” (t= 1.99, P< 0.05) significantly associated with impostor phenomenon. CONCLUSION: It is summarize that metacognitive skills play significant role in the development of fear related to success and impostor syndrome which can further lead to towards psychological distress and maladaptive coping mechanisms. Considering the findings implications and future directions have been suggested. KEYWORDS Metacognitive skills, impostor phenomenon, mental health problems.